The adventure of Iron Pussy - Weerasethakul, Apichatpong; Shaowanasai, Michael ([Thailand] Kick th Machine., 2003)
A transvestite secret agent is sent on a mission to the Thai countryside.
DVD
Writer, director : Michael Shaowanasai, Apichatpong Weerasethaku
Siriyakorn Pukkaresh, Michael Shaowanasai, Krissada Sukosol.
Keywords: Musical--Thailand.; Action films; Comedy films